REPRESENTATION STORY OF FAMILY, FRIENDSHIP AND RELATIONSHIP IN CINTA DAN RAHASIA ON NET TV - Citra Rani Angga Riswari; Nur’annafi Fsm (Metakom, 2018)
The phenomenon of Cinta dan Rahasia teleseries has finished but still get a place in the hearts of fans. In addition to the increasingly interesting conflicts, the thing that keeps many people from following this teleseries is the quotes from the players in each episode. The purpose of this research is to find out the representation story of family, friendship, and romance in teleseries. Qualitative research design with multimodal semiotics analysis approach was used in this research. The research subject was Cinta dan Rahasia teleseries on Net TV, object of the research was a scene that contained elements of family, friendship and romance. Data analysis technique with multimodal analysis with 2 stages, first, linguistic analysis, second visual analysis. The conclusion of this study showed that refresentative family stories, friendships, and romance in Cintadan Rahasia teleseries conducted by multimodal analysis methods yield results there is a multimodal semiotic system in these shows. Keywords: Teleseries CDR Net TV, Family Story, Friendship and love affair.